Encrypting an audio file based on integer wavelet transform and hand geometry - Zeena N. Al-Kateeb; Saja J. Mohammed (Universitas Ahmad Dahlan, 2020)
A new algorithm suggested for audio file encryption and decryption utilizing integer wavelet transform to take advantage of the property for adaptive context-based lossless audio coding. In addition, biometrics are used to give a significant level of classification and unwavering quality because the procedure has numerous qualities and points of interest. The offered algorithm utilized many properties of hand geometry estimations as keys to encode and decode the audio file. Many tests were carried out on a set of audio files and quality metrics such as mean square error and correlations were calculated which in turn confirmed the efficiency and quality of the work.